An Atypical Human Induced Pluripotent Stem Cell Line With a Complex, Stable, and Balanced Genomic Rearrangement Including a Large De Novo 1q Uniparental Disomy. (3rd February 2015) - Steichen, Clara; Maluenda, Jérôme; Tosca, Lucie; Luce, Eléanor; Pineau, Dominique; Dianat, Noushin; Hannoun, Zara; Tachdjian, Gérard; Melki, Judith; Dubart-Kupperschmitt, Anne
Abstract : The genomic integrity of human induced pluripotent stem cells (hiPSCs) is a barrier limiting their use in clinical applications. This article reports the characterization of an hiPSC line generated by daily transfections of modified messenger RNAs, displaying several genomic abnormalities. Single-nucleotide polymorphism analysis revealed the presence of a large 1q region of uniparental disomy (UPD), demonstrating for the first time that UPD can occur in a noncompensatory context during nonintegrative reprogramming of normal fibroblasts. Abstract: : Human induced pluripotent stem cells (hiPSCs) hold great promise for cell therapy through their use as vital tools for regenerative and personalized medicine. However, the genomic integrity of hiPSCs still raises some concern and is one of the barriers limiting their use in clinical applications. Numerous articles have reported the occurrence of aneuploidies, copy number variations, or single point mutations in hiPSCs, and nonintegrative reprogramming strategies have been developed to minimize the impact of the reprogramming process on the hiPSC genome. Here, we report the characterization of an hiPSC line generated by daily transfections of modified messenger RNAs, displaying several genomic abnormalities. Karyotype analysis showed a complex genomic rearrangement, which remained stable during long-term culture. Fluorescent in situ hybridization analyses were performed on the hiPSC line showing that this karyotype is balanced. Interestingly, single-nucleotide polymorphism analysis revealed the presence of a large 1q region of uniparental disomy (UPD), demonstrating for the first time that UPD can occur in a noncompensatory context during nonintegrative reprogramming of normal fibroblasts.